Long-Term Changes and Trends in the F2 Layer Critical Frequency over Alma-Ata (Kazakhstan) - Galina Gordiyenko; Artur Yakovets; Yurii Litvinov; Murat Zhiganbayev (Atmosphere)
The long-term variability and trends in the F2 layer critical frequency variations over Alma-Ata [43.25 N, 77.92 E] for the period 07.1957–04.2018 are studied using near-midday, near-midnight, and hourly median foF2 values. It is shown that the foF2 and solar activity index F10.7 display regular 11-year periodicity, stable negative trend over the 60-year observation interval, and some long-term (approximately four 11-year solar cycles) oscillation. The foF2 trend dependencies on the season and time of day are studied. The critical frequency shows a good connection with solar activity for the entire observation period and for each season. However, the position of the maximum in the time distribution of the difference between the observed foF2 and those calculated in accordance with the regression relationship between foF2 and F10.7 and smoothed with the 11-year window occurred earlier (around 1980) relative to the maximum in the F10.7 distribution (around 1986), which may indicate the influence of an additional (to solar activity) source on the ionosphere, possibly of an anthropogenic nature. The foF2 trend for 22-year periods before and after 1980 is investigated.